Posterior Dislocation of the Hinge-Post Extension in a Rotating Hinge Total Knee Prosthesis. (23rd September 2013) - Manzano, Givenchy; Schwarzkopf, Ran
Abstract : The rotating hinge knee prosthesis is a popular intervention in patients lacking stability with highly constrained total knee arthroplasty. Despite improvements in design, nonmechanical and mechanical complications continue to be a problem. Dislocation of the hinge has been widely described, mainly due to the component fracture. Few reports describe isolated dislocation of the rotating stem. We report a case of isolated disengagement of the rotating hinge mechanism, due to severe flexion gap imbalance, leading to subsequent posterior dislocation of the hinge and anterior knee dislocation, in a patient with a history of multiple total knee arthroplasty revisions. This case suggests the importance of the soft tissue balancing, the adequate patellar tracking, and use of a long cylindrical, minimally tapered rotating stem in hinge arthroplasty to minimize hinge dislocation.